UNJUK KERJA M-QAM PADA SISTEM DVB-T - , SHIFA JUNITA BELLAVY ([Yogyakarta] : Universitas Gadjah Mada, 2014)
DVB-T (Digital Video Broadcasting Terrestrial) is a first generation DTT (Digital Terresterial Television) standard developed by ETSI (European Telecommunications Standards Institute). It can be operated in the channel bandwidth of 6, 7, or 8 MHz, and has two options number of OFDM sub-carriers which are 2048 and 8192. OFDM (Orthogonal Frequency Division Multiplexing) is chosen since it can provide a large data capacity and multipath resistant. Using QPSK, 16-QAM, 64-QAM and 256-QAM modulation, the performance is monitored by comparing BER (Bit Error Ratio) value to SNR (Signal to Noise Ratio). Simulation has been carried out for 8 MHz bandwidth with Â¾ coding rate. The results show that zero BER achieved at SNR as high as 12 dB, 20 dB, 27 dB, and 29 dB for QPSK, 16, 64 and 256 QAMs, respectively. It should be noticed that QPSK and 256 QAM are not implemented in DVB-T.